THE ROLE OF PUBLIC RELATIONS IN BUILDING A COMPANY'S REPUTATION THROUGH THE CSR PROGRAM AT PT PLN IP UBP PRIOK - Mutiara Azka; RR. Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Corporate Social Responsibility (CSR) is a strategic approach that enables companies to strengthen relationships with communities while enhancing corporate reputation. The successful implementation of CSR is closely related to the role of Public Relations as a managerial function responsible for managing communication and stakeholder relationships. This study aims to analyze the implementation of Public Relations roles in the Pesona Betawi CSR Program and their contribution to the corporate reputation of PT PLN Indonesia Power UBP Priok. A qualitative case study approach was employed. Data were collected through in-depth interviews, observations, and documentation involving five informants selected using purposive sampling. Data were analyzed through data reduction, data display, and conclusion drawing with source triangulation to ensure credibility. The findings indicate that Public Relations implemented the four roles proposed by Dozier and Broom throughout the planning, implementation, and evaluation stages of the Pesona Betawi CSR Program. These integrated roles strengthened the relationship between the company and the community and contributed to building a positive corporate reputation.